Thymic Stromal Lymphopoietin (TSLP) gene variant rs1837253 is significantly associated with Asthma prevalence in Pakistani Pashtun women - Afzal, Sibtain; Ramzan, Khushnooda; Khan, Ihsanullah; Ullah, Anhar; Tahir, Asma I; Ramzan, Shaiqa; Ullah, Sajjad; Jamal, Arshad; Absar, Muhammad; Basit, Sulman; Waqar, Ahmed Bilal (Pakistan journal of pharmaceutical sciences, 2020)
Asthma is a chronic inflammatory disease of the airways characterized by airway hyperresponsiveness and remodeling. Thymic stromal lymphopoietin (TSLP), a member of the interleukin-2 family of cytokines, is produced by activated lung and intestinal epithelial cells, mast, and other immune cells. Population-based studies identified associations between SNPs in the TSLP promoter region and asthma pathogenesis. In this study, we analyzed the genotypic association of TSLP rs1837253 with asthma predisposition in the Pashtun population of Khyber Pakhtunkhwa, Pakistan. Target DNA sequence of 250 asthmatics and an equal number of healthy individuals was PCR amplified, and allelic determination was performed by Sanger sequencing. Statistical analysis was conducted using chi-square tests and logistic regression analysis. Homozygous T/T genotype was frequent in the asthmatic subjects with a statistically significant level (P<0.05). Genetic models, including recessive, dominant, co-dominant, over-dominant, and additive were tested while adjusting allele frequencies with covariates (gender and age). Combined C/T and T/T individuals had higher odds ratios of 3.00, 1.91, and 1.73 in co-dominant, dominant, and additive models with statistically significant P-values of 0.029*, 0.022*, and 0.02*, respectively. T allele of rs1837253 was associated with increased susceptibility to asthma among Pashtuns, particularly in females, and we corroborate rs1837253 as a SNP of interest with a potential functional role.